Targeting the dendritic cell-T cell axis to develop effective immunotherapies for glioblastoma - Gardam, Bryan; Gargett, Tessa; Brown, Michael P.; Ebert, Lisa M. (Frontiers in Immunology, 2023)
Glioblastoma is an aggressive primary brain tumor that has seen few advances in treatments for over 20 years. In response to this desperate clinical need, multiple immunotherapy strategies are under development, including CAR-T cells, immune checkpoint inhibitors, oncolytic viruses and dendritic cell vaccines, although these approaches are yet to yield significant clinical benefit. Potential reasons for the lack of success so far include the immunosuppressive tumor microenvironment, the blood-brain barrier, and systemic changes to the immune system driven by both the tumor and its treatment. Furthermore, while T cells are essential effector cells for tumor control, dendritic cells play an equally important role in T cell activation, and emerging evidence suggests the dendritic cell compartment may be deeply compromised in glioblastoma patients. In this review, we describe the immunotherapy approaches currently under development for glioblastoma and the challenges faced, with a particular emphasis on the critical role of the dendritic cell-T cell axis. We suggest a number of strategies that could be used to boost dendritic cell number and function and propose that the use of these in combination with T cell-targeting strategies could lead to successful tumor control.